Multiple omnidirectional reflection bands from half-wave layered periodic structures - Cojocaru, E. (Oficyna Wydawnicza Politechniki Wrocławskiej, 2005)
The paper is concerned with one-dimensional multilayers that exhibit multiple bands of omnidirectional reflection, which means complete reflection regardless of incidence angle and polarization. The typical quarter-wave constraint is replaced by the stipulation that a pair of adjacent layers should have a total optical thickness of one half of wavelength. Simple approximate analytic expressions are derived for the multiple bandgaps of the half-wave periodic structures.
Optica Applicata, Vol. 35, 2005, nr 2, s. 201-207
Keywords: optyka; thin films; multilayers; filters; bandgaps; 1D photonic crystals